Data Mining Prediksi Produksi Garam Pada Pertanian Tradisional Menggunakan Algoritma C4.5 - Rian Hidayatullah; Achmad Udin Zailani (CV. Multi Kreasi Media, 2023)
Data mining is an automated process of existing data. The data to be processed is a very large amount of data. The goal of data mining is to find relationships or patterns that might provide useful information. One of these efforts is to calculate the potential for salt production as accurately as possible so that it will be known how much information is predicted for salt production in several areas. The problems faced by farmers are not only about not being able to produce suitable salt for industrial salt, but also the problem of the area of salt farmers' land and the unpredictable weather in Indonesia. This study applies the C4.5 algorithm. This method is to get predictions of production in conventional salt farming. The results of this research and testing show that there is an increase in salt production in 2019 compared to 2018.